Analisis Pemanfaatan Teknologi Informasi Di Klink Penta Medica Menggunakan Framework Cobit 5 Pada Domain DSS - Aditya, I Gede Aditya Mahardika; Putri Anugrah Cahya Dewi (Primakara University, 2021)
Information Technology (IT) as a support to improve efficiency and effectiveness in the company's operational processes. The application of information technology is a supporting instrument in the operations of companies engaged in all fields. To ensure the correct application of information technology and support corporate goals as well as to be effective and efficient in its operations, information technology governance is required. information technology governance process that has been carried out, it can be concluded that the results of the recapitulation of the level of information technology governance capability model at the PENTA Medica Clinic are level 3 (Define Process) and level 4 (Managed and Measurable) with the following process details: Manage operations (DSS01), and Manage service requests and incidents (DSS02) are at level 3; Manage problems (DSS03), Manage continuity (DSS04), Manage security service (DSS05), Manage business process controls (DSS06) are at level 4. This means that information technology at the PENTA Medica Clinic has been implemented into a managed model with work products according to existing information technology services.